2021
DOI: 10.1503/jpn.200151
|View full text |Cite
|
Sign up to set email alerts
|

Elevated activity in the dorsal dentate gyrus reduces expression of fear memory after fear extinction training

Abstract: Background: Effectively reducing the expression of certain aversive memories (fear or trauma memories) with extinction training is generally viewed to be therapeutically important. A deeper understanding of the biological basis for a more effective extinction process is also of high scientific importance. Methods: Our study involved intraventricular injection or local injection into the dorsal dentate gyrus of anti-neuregulin 1 antibodies (anti-NRG1) before fear extinction training, followed by testing the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…To confirm that the recorded neurons is PV-positive, we performed immunofluorescence staining. 43 Slices were fixed with 4 % paraformaldehyde for 24 hr, then were dehydrated in 30% sucrose for 48 hr at 4 ℃. The sections were washed with PBS three times and 10 mins each.…”
Section: Whole Cell Recordingmentioning
confidence: 99%
“…To confirm that the recorded neurons is PV-positive, we performed immunofluorescence staining. 43 Slices were fixed with 4 % paraformaldehyde for 24 hr, then were dehydrated in 30% sucrose for 48 hr at 4 ℃. The sections were washed with PBS three times and 10 mins each.…”
Section: Whole Cell Recordingmentioning
confidence: 99%
“…The axons of newborn neurons, known as mossy fibers, are connected to synapses with excitatory pyramidal cells in the CA3 and CA2 regions. Synaptic integration sets a time constraint on the contributions of newborn DGCs to neuronal circuitry in the adult brain [ 16 , 17 ]. Functionally mature newborn neurons are integrated into existing circuits and incorporated into the hippocampal network, which plays a critical role in long-term spatial learning and memory, pattern separation, anxiety, and fear generalization [ 18 , 19 ].…”
Section: Fear Memory and Overgeneralization In The Hippocampusmentioning
confidence: 99%
“…This indicates that the ACC and ventral hippocampus, via projections to the basolateral amygdala, regulate fear generalization. Zhang et al found that the chemogenetic inhibition of excitatory neuronal activity in the dorsal DG of the hippocampus is directly related to a higher expression of fear memory [ 17 ]. In contrast, enhancing neuronal activity in the dorsal DG using DREADDs (hM3D) or optogenetic stimulation reduced the percentage of freezing time, suggesting a reduced expression of fear memory.…”
Section: Hippocampus-related Neural Circuits In Fear Memorymentioning
confidence: 99%